PENGARUH LKPD DISCOVERY LEARNING BERBASIS ETNOMATEMATIKA TERHADAP HASIL BELAJAR SISWA DITINJAU DARI BERPIKIR REFLEKTIF - Muhamad Toyib; Sania Zulias Silva Sari; Nuqthy Faiziyah (Jurnal Inovasi Matematika, 2026)
The purpose of this study is to analyze the effect of worksheet-based learning using the discovery learning approach with the Joglo House ethnomathematics approach on students’ learning outcomes in geometric transformations, specifically in the chapters on rotation and reflection; the effect of mathematical reflective thinking skills on learning outcomes categorized as high, medium, or low; and the interaction between the learning model and reflective thinking skills. This study employed a quasi-experimental method with a factorial design 2 x 3 . The study population consisted of ninth-grade junior high school students, with the sample selected using cluster random sampling. Data were collected through learning achievement tests and reflective thinking assessments in essay format. Hypothesis testing was conducted using a two-way ANOVA with unequal cells at a significance level of  0.5 %. The results of the study indicate that discovery learning based worksheets using the Joglo House ethnomathematics approach have a significant effect on student learning outcomes. Mathematical reflective thinking skills also have a significant effect on learning outcomes. However, there is no interaction between the learning model and reflective thinking skills on learning outcomes. This study demonstrates that the learning model and reflective thinking skills contribute independently to improving mathematics learning outcomes.